Pengaruh profitabilitas, likuiditas, dan price earning ratio terhadap nilai perusahaan - Nurindrayani, Aulya; Indrati, Menik (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The COVID-19 pandemic has had an impact on the activities of Indonesian manufacturing companies, even though the impact of the COVID-19 pandemic has not directly affected the company's value, which is associated with share prices, but has instead affected company profits. The purpose of this study is to analyze the effect of profitability, liquidity, and price-earnings ratio on firm value. This study uses descriptive statistical methods with data analysis techniques such as multiple regression analysis using the Statistical Package for the Social Sciences (SPSS). In this study, 35 companies met the criteria from a total population of 39 manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period were sampled. These results indicate that the profitability variable has no effect on firm value, the liquidity variable has a positive effect on firm value, and the price-earnings ratio has a positive effect on firm value. This research can provide advice to shareholders about paying close attention to the company's value regarding financial and management information published by the company when making decisions about purchasing company shares.